26 Designing safer services for patients needing palliative care in gp out of hours services: a national analysis of patient safety data to identify priorities for systems improvement. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Williams, Huw; Noble, Simon; Edwards, Adrian; Kenkre, Joyce; Hibbert, Peter; Donaldson, Liam; Carson-Stevens, Andrew
Abstract : Background: Patients receiving OOH palliative care are at increased risk of unsafe care (Mazzocato & Stiefe, l 1997; Dietz et al. 2010). The identification of improved ways of delivering palliative care outside working hours is a priority area for policy makers. (Best et al. 2015) To allow service redesign to provide safer care for patients, a means of identifying priority areas for systems improvement is needed. Aims: Explore the nature and causes of unsafe care delivered to patients receiving palliative care from primary care services outside normal working hours. Review literature to identify existing interventions addressing causes of unsafe care. Engage a stakeholder group in a large healthcare organisation in Wales to identify priority areas within the out–of–hours GP service. Methods: We characterised patient safety incident (PSI) reports submitted to the National Reporting and Learning System, using codes to describe what happened, underlying causes, harm outcome, and severity of harm. Exploratory descriptive and thematic analyses identified factors underpinning unsafe care. Results of this analysis informed a scoping review of the literature (Tricco et al. 2016), and findings were presented as a driver diagram (a one-page summary of where and how to improve the system). Results: 1072 reports of suboptimal care, described: medication-related issues (n=613); access to timely care (n=123); and non-medical management of pressure ulcers or urinary catheters. (n=102). Almost two thirds of reports (n=695) described harm with outcomes including increased pain, distress and dying in a place not of their choosing. A scoping review identified interventions to improve confidence of staff around end of life medications, improve advanced care planning and improve documentation across providers. The driver diagram facilitated discussions amongst stakeholders (lay and professional) to contextualise findings and identify priorities for service improvement. Conclusions: Analysis of PSI reports and associated literature review can be used to inform service improvement initiatives.